Revealing New Truths about Spain's Violent Past Perpetrators' Confessions and Victim Exhumations - Aguilar, Paloma; Payne, Leigh A.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
The foundation of a stable democracy in Spain was built on a settled account: an agreement that both sides were equally guilty of violence, a consensus to avoid contention, and a pact of oblivion as the pathway to peace and democracy. That foundation is beginning to crack as perpetrators' confessions upset the silence and exhumations of mass graves unbury new truths. It has become possible, even if not completely socially acceptable, to speak openly about the past, to disclose the testimonies of the victims, and to ask for truth and justice. Contentious coexistence that put political participation, contestation, and expression in practice has begun to emerge. This book analyzes how this recent transformation has occurred. It recognizes that political processes are not always linear and inexorable. Thus, it remains to be seen how far contentious coexistence will go in Spain.
Acknowledgements -- Introduction -- 1. Unsettling Accounts -- 2. Heroic Historic Confessions -- 3. Few, Fugative, and Fleeting Confessions -- 4. Unsettling the Balance -- 5. Preposterous Denial -- 6. Unsettling Bones as Unsettling Accounts -- Conclusion.
Keywords: Europe-History-1492-.; History of Modern Europe